ANALISIS PENINGKATAN KEPUASAN MAHASISWA TERHADAP TEAM TEACHING MATA KULIAH DEPARTEMEN MANAJEMEN TEKNOLOGI ITS - Noer, Lissa Rosdiana (Universitas Nahdlatul Ulama Sidoarjo, 2017)
Improving students’ satisfaction to the subjects team teaching of ITS Technology Management Department needs to do assessment using Gap Analysis. It was chosen to find out the expectation and reality that students felt to academic service provided by subject team teaching. The expertise areas that this department has are: Industrial Management, Project Management, and Information Technology Management. Total subjects are 23 pursued by 2nd, 3rd, and 4th semester students who were research respondents. The data processing results show that there were 17 subjects with valid data. Enhancements needed to improve students’ satisfaction are by implementating midterm exam, final exam, and task (presentation) on schedule, giving lecture material according to the expertises, giving clear and understandable lecture material, giving subjects literature, performing objective and transparent assessment, explaining lesson plan, holding lecture on schedule, being able to understand students’ characteristic, being available for discussion outside the class meetings, accepting criticism and suggestion.